PENGARUH SELF-REGULATED LEARNING, GOAL ORIENTATION DAN KECERDASAN EMOSIONAL TERHADAP PRESTASI BELAJAR PADA SISWA KELAS V SEKOLAH DASAR ISLAM AL-AZHAR 5 KEMANDORAN JAKARTA - Nuri Setiyaningsih (Fakultas Psikologi Universitas Borobudur, 2021)
This study aimed of self-regulated learning, goal orientation and emotional intelligence to thestudent achievement. The subject were fifth grade student at Al Azhar 5 Kemandoran many as 120students. In this study using stepwise method by showing the result of variable goal orientation Rsquare change = 0,291 showing 0,291 x 100% =29,1 % and variable emotional intelligenceshowing the result R square change = 0,092 showing 0,092 x 100 % = 9,2 % , while the variable slfregulated learning the contribute only small so do not look at the SPSS program. Based on thisstudy we can conclude the research hypothesis on three variables only goal orientation andemotional intelligence that’s gives effect to the achievements a learning.Key word: emotional question, goal orientation, learning achievemment, self reguated learning